2022
DOI: 10.1073/pnas.2111064119
|View full text |Cite
|
Sign up to set email alerts
|

Strong influenza-induced T FH generation requires CD4 effectors to recognize antigen locally and receive signals from continuing infection

Abstract: While influenza infection induces robust, long-lasting, antibody responses and protection, including the T follicular helper cells (TFH) required to drive B cell germinal center (GC) responses, most influenza vaccines do not. We investigated the mechanisms that drive strong TFH responses during infection. Infection induces viral replication and antigen (Ag) presentation lasting through the CD4 effector phase, but Ag and pathogen recognition receptor signals are short-lived after vaccination. We analyzed the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…It has long been appreciated that while infection by influenza virus induces robust and long-lived humoral responses, seasonal influenza vaccination strategies have largely failed in this regard. Devarajan and colleagues speculated that this could be due to differences in antigen availability and duration of Tfh responses in the LNs between influenza infection and vaccination with inactivated vaccines ( Devarajan et al., 2022 ). Their 2022 study found that strong influenza-induced Tfh responses require CD4 effectors to continually recognize local antigens and receive signals from ongoing infection ( Devarajan et al., 2022 ).…”
Section: Adaptive Respiratory Immune Response: Priming Antigen-specif...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been appreciated that while infection by influenza virus induces robust and long-lived humoral responses, seasonal influenza vaccination strategies have largely failed in this regard. Devarajan and colleagues speculated that this could be due to differences in antigen availability and duration of Tfh responses in the LNs between influenza infection and vaccination with inactivated vaccines ( Devarajan et al., 2022 ). Their 2022 study found that strong influenza-induced Tfh responses require CD4 effectors to continually recognize local antigens and receive signals from ongoing infection ( Devarajan et al., 2022 ).…”
Section: Adaptive Respiratory Immune Response: Priming Antigen-specif...mentioning
confidence: 99%
“…Devarajan and colleagues speculated that this could be due to differences in antigen availability and duration of Tfh responses in the LNs between influenza infection and vaccination with inactivated vaccines ( Devarajan et al., 2022 ). Their 2022 study found that strong influenza-induced Tfh responses require CD4 effectors to continually recognize local antigens and receive signals from ongoing infection ( Devarajan et al., 2022 ). GC reactions stalled with inactivated vaccination but could be prolonged with the administration of LAIV.…”
Section: Adaptive Respiratory Immune Response: Priming Antigen-specif...mentioning
confidence: 99%
“…To evaluate the subsets of CD4 effectors generated, we compared donor and host CD4 effectors at 8 dpi by examining cytokine production and phenotype markers: Th1 (T-bet, IFNγ, TNFα, IL-2), Triple cytokine producers (IFNγ, TNFα, IL-2), Th17 (IL-17), and T REG (FoxP3). We used NKG2A/C/E expression to detect cytotoxic CD4 (ThCTL), found only in the lung (31), and CXCR5 and Bcl-6 co-expression markers for T FH in the spleen (32) (Fig. 1B, Supp.…”
Section: Resultsmentioning
confidence: 99%
“…Transfer of Ag/APC i.n. successfully restricted Ag presentation to the lung, while transfer of Ag/APC i.s restricted Ag presentation to the spleen (Devarajan et al, 2022) (summarized in Figure S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous data show that after intravenous (i.v.) OVA II /APC transfer they are found predominantly in the spleen and not in the lung, though donor effectors in the lung express Nur77 GFP , suggesting that they recognized Ag in the periphery before migrating to the lung (Devarajan et al, 2022) ( Figure S4A ). To test if peripheral Ag presentation was sufficient to drive 6d effectors to ThCTL, we transferred OVA II /APC i.v.…”
Section: Resultsmentioning
confidence: 99%